Winter crop residues and N assimilation by summer crops - Heinzmann, Franz X. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of winter cover crops (Lupinus allbus L., Vicia villosa Roth, Avena strigosa Schieb. and Raphanus sativus L),wheat and fallow on the nitrate content of the soil and N assimilation in following crops of beans, soybeans and corn was studied on an Oxisol. Eight weeks after cutting the winter cover crops, NO-3 -N content of the soil varied from 18 to 149 kg/ha for the fallow and Raphanus sativus treatments, respectively. Under trial conditions nitrate movement to a depth of 60 cm - 90 cm was observed. The relationship between the nitrate content of the soil and the total N in harvested crops was significant for corn only. The results showed that if other agronomic factors permit corn, beans or soybeans should be planted as soon as possible after cutting the winter cover crops. A C/N ratio of winter cover crops residues of about 23-24 was shown to be adequate for corn resulting in a uniform mineralization of N. For leguminous crops, the C/N ratio should be greater than 25 in order to produce a stable mulch cover, and favourable conditions for nodule formation and function.